(untitled) (Doctor Virtualis, 2021)
Considering Umberto Eco’s articles and novels, the paper will examine the imaginary of the Middle Age as the cradle of every kind of millenarianism. The analysis will start from Eco’s essay Palinsesto su Beato (1963). Looking at the originality of his structuralist view, I will compare the last editing of this text with a bibliographical framework about the role of the Apocalypse of St. John in the Western tradition. The first reference will be the genealogical thesis of Karl Löwith, who in Meaning in History (1949) affirmed that the modern philosophies of history have the same eschatological aim of the Christian culture. The second comparison will be with a portrait of the medieval heresiarch Fra Dolcino. In this case, I will consider the perspective of the socialist philosopher Antonio Labriola, who elaborated it at the end of the XIX Century to distinguish the scientific applications of historical materialism from his eschatological misinterpretations. These two opposite references will drive me to problematize the representation of millenarianism as it was depicted by Umberto Eco in his The Name of the Rose (1980). Indeed, is Dulcinian millenarianism intended by the novel as a prefiguration of the political terrorism in Italy during the Years of Lead? Or is this only a wink, a joking interaction with the reader, who should be careful to rely not on the symbolic strength of analogies?